1997
DOI: 10.1093/jpepsy/22.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Verbal Short-Term Memory Deficits in Childhood Leukemia Survivors After Intrathecal Chemotheraphy

Abstract: Assessed survivors of childhood lymphoblastic leukemia (ALL) treated with intrathecal chemotherapy, using the Wide Range Assessment of Memory and Learning (WRAML), compared to controls without cancer, matched as closely as possible in age, SES, and gender. Mild, but consistent, deficits were found in both visual-spatial and verbal single-trial memory tasks. In multitrial learning, only visual-spatial tasks resulted in deficient scores, while verbal learning was within the normal range. IQ results indicated sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 20 publications
3
49
0
1
Order By: Relevance
“…Even though the poor prognostic impact of traumatic lumbar puncture can be abolished by intensive systemic and intrathecal therapy, 15 every effort should be made to prevent its occurrence because intrathecal therapy can also adversely affect neuropsychologic and spinal cord functions. 32,33 Since recognition of the adverse consequences of traumatic lumbar puncture, 34 we correct thrombocytopenia before the diagnostic lumbar puncture, which is followed immediately by intrathecal treatment. Finally, intrathecal therapy is routinely performed by the most experienced clinician in our center, with patients under deep sedation or general anesthesia.…”
Section: Intrathecal Therapymentioning
confidence: 99%
“…Even though the poor prognostic impact of traumatic lumbar puncture can be abolished by intensive systemic and intrathecal therapy, 15 every effort should be made to prevent its occurrence because intrathecal therapy can also adversely affect neuropsychologic and spinal cord functions. 32,33 Since recognition of the adverse consequences of traumatic lumbar puncture, 34 we correct thrombocytopenia before the diagnostic lumbar puncture, which is followed immediately by intrathecal treatment. Finally, intrathecal therapy is routinely performed by the most experienced clinician in our center, with patients under deep sedation or general anesthesia.…”
Section: Intrathecal Therapymentioning
confidence: 99%
“…Six of the studies conclusively showed that ALL survivors experienced deficits in neurocognitive functioning when compared with age-matched healthy controls (Table 1), which was attributed to their chemotherapy-only treatment. 19,28,[31][32][33] The other 4 studies found either very small differences or differences that were not statistically significant when compared with the healthy control group. Intelligence or overall cognitive ability was measured by 8 studies.…”
mentioning
confidence: 94%
“…Six of the 10 studies used a cross-sectional design, identified participants at some point after remission was established, and conducted at least 1 neurocognitive assessment after completion of treatment. 27,28,[31][32][33][34] The other 4 studies used a longitudinal design, identified patients at diagnosis, and completed periodic neurocognitive assessments during treatment and off therapy. 11,19,29,30 Collectively, the study population included in the analyses had a mean age at diagnosis of 4.4 years (median, 4.0), a mean age at last evaluation of 11.7 years (median, 10.3), and a mean time since diagnosis of 8.0 years (median, 8.2).…”
mentioning
confidence: 99%
“…7,13 In addition, long-term difficulties in cognitive and academic function are often described, 22 most frequently visual perceptual, attention, and math skills. 10,13,[23][24][25][26][27][28][29][30][31][32][33][34][35] Voxel-based morphometry (VBM) is an automated method for analyzing whole brain regional differences on a voxel-by-voxel basis. The purpose of this study was to use VBM to examine regional white and gray matter differences in a group of long-term survivors of ALL treated with systemic and intrathecal chemotherapy, compared with a group of healthy controls, and to examine the relationship of regional brain volumes to cognitive function.…”
mentioning
confidence: 99%